EXTENDED LAND-TENURE RIGHTS IN NUSANTARA: A LEGAL ANALYSIS OF REGULATORY INCONSISTENCY AND AGRARIAN JUSTICE - Alif Abdurrahman; Budi Santoso; Ery Agus Priyono (Jurnal Hukum Progresif, 2026)
Indonesia’s relocation of its national capital to Nusantara, East Kalimantan, has created a special land-tenure regime designed to accelerate development and attract investment. Under the general agrarian framework established by Law No. 5 of 1960 and Government Regulation No. 18 of 2021, the maximum cumulative duration of the Right to Cultivate is 95 years, while the Right to Build may be granted for up to 80 years. By contrast, the special regulations governing Nusantara allow these rights to extend to 190 years and 160 years, respectively. This study analyses the normative inconsistencies between the national agrarian regime and Nusantara’s special legal framework, as well as their implications for legal certainty, land-rights protection, agrarian justice, and sustainable land governance. It employs a doctrinal legal method using statutory, conceptual, and philosophical approaches. Primary and secondary legal materials are examined qualitatively through grammatical, systematic, and teleological interpretation, supported by deductive reasoning and Hans Kelsen’s hierarchy of norms theory. The findings show that the extended tenure schemes may be defended under the principle of lex specialis derogat legi generali. Nevertheless, their substantial departure from the Basic Agrarian Law creates tension concerning regulatory hierarchy, the social function of land, and the State’s constitutional duty to manage natural resources for the greatest prosperity of the people. The policy may also concentrate land control in business entities, restrict access for local and Indigenous communities, intensify agrarian disputes, encourage speculation, and accelerate environmental degradation. Although long-term tenure may strengthen investor confidence, it should not weaken public oversight, customary rights, or agrarian justice. The study concludes that harmonisation between Nusantara’s special regulations and national agrarian principles is essential. Periodic evaluation, transparent allocation, meaningful community participation, environmental safeguards, recognition of customary tenure, and enforceable obligations for rights holders are required to ensure legally coherent, socially equitable, and environmentally sustainable development.